Late Cretaceous (Maastrichtian) foraminiferal assemblage from the inoceramid beds, Ocozocoautla Formation, central Chiapas, SE Mexico - Lourdes Omaña (Revista Mexicana de Ciencias Geológicas)
Foraminifera from samples collected in the lower part of the Ocozocoautla Formation were studied. This sequence crops out north-west of Tuxtla Gutiérrez in central part of Chiapas state in south-eastern Mexico. The lower part of the unit consists mostly of argillaceous and marly sandstone with inoceramids. This horizon yields a poorly preserved but biostratigraphically useful foraminiferal assemblage.